Montenegro joins the line of concordats with the Holy See. Development of concordats in the last decades - Santos Díez, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
On the occasion of signing the Concordat between the Holy See and Montenegro, whose main characteristics are pointed out, but previously a general view of the development of concordats in the last five years and its most important regulating contents are pointed out.